RESTORATIF JUSTICE PADA KASUS KEKERASAN DALAM RUMAH TANGGA MENURUT PERSPEKTIF HUKUM PIDANA ISLAM - Ahmad Syairafi Al Ayyubi; erniwati erniwati (Tazir, 2023)
Restorative Justice is a settlement process that is carried out outside the criminal justice system by involving victims, perpetrators, families, communities and parties involved in this case in domestic violence cases in order to achieve agreement and peace between the parties. The number of cases that appear in the news is proof that there is still a lot of domestic violence that occurs in Indonesia, while the efforts made to solve the problem of domestic violence are through restorative justice. The main point of study in this research is how to stop the prosecution of husbands who commit domestic violence cases according to Perja Number 15 of 2020 and the views of Islamic criminal law on stopping prosecution of husbands who commit domestic violence cases. The purpose of this study is to find out the termination of criminal cases against husbands of domestic violence perpetrators according to restorative justice according to Perja Number 15 of 2020 and to find out the perspective of Islamic criminal law regarding stopping prosecution of husbands of perpetrators of domestic violence regarding restorative justice. This type of research uses normative juridical research with qualitative methods to analyze legal principles and theories and uses secondary data sources in collecting the necessary data. The results of this study are that the Termination of Prosecution for the husband of the perpetrator of a domestic violence case is further regulated in the Prosecutor's Office Regulation Number 15 of 2020. The prosecutor's office can legally and properly invite the victim to reconcile by stating the reason for the summons (Articles 7 & 8 Perja Number 15 of 2020). And the reconciliation process is carried out voluntarily without pressure and threats (Article 9 Prosecutor's Regulation No. 15 of 2020) in the event that the victim and the defendant reach an agreement to make peace which is recorded before the Prosecutor's Office (Article 10 of the Prosecutor's Regulation No. 15 of 2020). The perspective of Islamic criminal law restorative justice in the prosecutor's regulation is in accordance with the concept of islah in Islamic criminal law. Where the husband of the perpetrator of domestic violence tries to apologize to the victim & promises not to repeat his actions. Keywords: Domestic Violence, Restorative Justice, Islamic Criminal Law.